Citation Practices in Colombian Undergraduate English Teachers’ Academic Writing - Salazar Obeso, Wilmar (ELT Worldwide: Journal of English Language Teaching, 2023)
Citation is a crucial rhetorical aspect that plays a fundamental role within academic writing and it is a problematic area for novice writers, especially nonnative undergraduate English   teachers. However, little is known about how these teachers cite in the theoretical framework chapters of their monograph. This articles aims at describing the citation practices in a corpus conformed by 22 theoretical framework chapters of monographs written by undergraduate English teachers (UETs) in Colombia. The analysis was constituted by the citation typology of Swales (1986,1990) and Petriḉ’s (2007) functional taxonomy of citations.  The results indicate that integral citation is the most used citation type in the corpus of UETs which depicts a simple for of citation. Related to functions, the attribution is highly dominant   in this corpus which entails an undergraduate English teachers’ limitation in the variety of function citation. This study can be used to raise awareness on nonnative undergraduate English teachers towards better citation practices in their disciplinary academic papers.